Integration of Central, East, West Java and Jakartas Shallot Market - Siti Sholihah; Karsinah Karsinah (Economics Development Analysis Journal, 2019)
The purpose of this study was to know and analyze the shallot markets of Central Java with shallot markets in East Java, Jakarta, and West Java. The method of data analysis in this study is the Johansen Cointegration Test, Causality Test, and Vektor Error Correction Model (VECM). The data used is secondary data in the form of monthly sources from the Central Statistics Agency and the Ministry of Agriculture. The results of the research are producer markets and consumer markets in Central Java are integrated, the Central Java producer market and the East Java consumer market, Jakarta consumer market, and West Java consumer market are integrated, the Central Java consumer market and East Java consumer market, Jakarta consumer market, and West Java consumer market are integrated. Based on the trial of the causality of market integration carried out is weak, only the consumer market integration of Central Java with East Java consumer market is strong. Based on the results of the VAR / VECM analysis shows that adjustment of the prices of shallots in Central Java producer market slower than adjustments of the price of Central Java, East Java, and Jakarta consumer markets. Efforts to overcome this problem can be done by increasing the implementation of policies on the floor price and the ceiling price.